Piper Nigrum Extract as an Environmentally-Safe Inhibitor for the Prevention of Mild Steel in 1.5 M Nitric Acid Medium - Balamurugapandian, N. (Journal of Scientific Research, 2021)
Piper nigrum has extensively explored for its biological properties and its bioactive phyto-compounds. The corrosion prevention of mild steel by Piper nigrum extract (black pepper) using 1.5 M nitric acid medium was examined by the weight-loss method, scanning electron microscope (SEM) examination. The consequences of the study reveal that the dissimilar concentrations of extract prevent mild steel corrosion in acidic medium. The Inhibition efficiency of the extract is found to vary with concentration, temperature, and time of immersion. The inhibition efficiency of the extract was directly proportional to the concentration but inversely proportional to the temperature. Scanning electron microscope experiments exhibit the adsorption of the inhibitory properties of black pepper extract on the surface of the mild steel and show the evidence for the protection of Mild steel by the eco-friendly inhibitor. FTIR values also show evidence for the inhibition of Mild Steel.